VALIDATED RP-HPLC METHOD AND UNIQUE MOBILE PHASE FOR THE SIMULTANEOUS ESTIMATION OF AMLODIPINE BESYLATE AND VALSARTAN FROM SOLID DOSAGE FORM AND ROSUVASTATIN AND VALSARTAN FROM BULK - DYADE GK; RL, SAWANT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: A reverse-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the simultaneous estimation of amlodipine besylate (AD) and valsartan (VAL) in pharmaceutical dosage form, and rosuvastatin (RV) and VAL from the bulk mixture. Method: Chromatographic separation was performed on RP-C18 column. The optimized unique mobile phase (acetonitrile:water and pH adjusted to 4.8 with acetic acid) was pumped at a flow rate of 0.8 ml/min in the ratio of 75:25% v/v, and the eluents were monitored at 245 nm. Results: The assay was performed with tablet and percentage of assay was found to 101.39 for AD and 100.05 for VAL, respectively, and with bulk mixture, percentage of assay was found to 99.58 for RV and 100.32 for VAL, respectively. Linearity was obtained in the concentration range of 1–12 μg/ml for AD, 5–50 μg/mL for VAL, and 2–20 μg/ml for RV. The method was statistically validated and RSD was found to be <2%, indicating high degree of accuracy and precision of the proposed RP-HPLC method. Conclusions: The method suggests usefulness of unique mobile phase during the estimation of two or more multicomponent dosage forms. Due to its simplicity, rapidness, high precision, and accuracy, the proposed RP-HPLC method can be applied for simultaneous determination of AD and VAL in pharmaceutical dosage form, and RV and VAL in bulk mixture.